Comportamento da cultura do feijão (Phaseolus vulgaris L.) no outono-inverno - Chagas, José Mauro; Vieira, Clibas; F Bártholo, Gabriel (Revista Ceres, 2025)
The bean cultivars ‘Vi. 1010, ‘Ricobaio 1014’, ‘Carioca’, ‘Negrito 897’, ‘Milionario 1732, and ‘Rico 1735’ were planted at intervals from April to June, with irrigation, at Ponte Nova, State of Minas Gerais, in order to study their performances during the fall-winter. This practice was found to be feasible. Some cultivars in some planting dates attained yields of 1,800 to 2,200 kg/ha. Such yields are not easily obtained in the traditional planting times, when the crop depends entirely on the rainfall. The interaction cultivar x planting date was highly significant.